Hearing Written Magic in Harry Potter Films: Insights into Power and Truth in the Scoring for In-World Written Words - Jamie Lynn Webster (Humanities)
This paper explores how sound design in the Harry Potter film series shapes the symbolic significance of written words within the magical world. Sound mediates between language and meaning; while characters gain knowledge by reading and seeing, viewers are guided emotionally and thematically by how these written texts are framed through sound. For example, Harry’s magical identity is signalled to viewers through the score long before he fully understands himself—first through music when he speaks to a snake, then more explicitly when he receives his letter from Hogwarts. Throughout the series, characters engage with a wide array of written media—textbooks, letters, newspapers, diaries, maps, and inscriptions—that gradually shift in narrative function, from static props to dynamic, multi-sensory agents of transformation. Using a close analysis of selected scenes to examine layers of utterances, diegetic sounds, underscore, and sound design, this study draws on metaphor theory and adaptation theory to examine how sound design gives writing a metaphorical voice, sometimes framing it as character, landscape, or moral authority. As the series progresses, becoming more autonomous from the literary source, written words take on greater symbolic significance, and sound increasingly determines which texts are granted narrative power, whose voices are trusted, and how viewers interpret truth and agency across media. Ultimately, written words in the films are animated through sound into agents of growth, memory, resistance, and transformation. Thus, the audio-visual treatment of written magic reveals not just what is written, but what matters.